Oxygen‐Linked Cyclopentadienyl Rhodium(III) Complexes‐Catalyzed Asymmetric C−H Arylation of Benzo[h]quinolines with 1‐Diazonaphthoquinones - Pan, Chongqing; Yin, Si‐Yong; Wang, Shao‐Bo; Gu, Qing; You, Shu‐Li (Angewandte Chemie International Edition, 2021)
Chiral cyclopentadienyl rhodium (CpRh) complex‐catalyzed asymmetric C−H functionalization reactions have witnessed a significant progress in organic synthesis. In sharp contrast, the reported chiral Cp ligands are limited to C‐linked Cp and are often synthetically challenging. To address these issues, we have developed a novel class of tunable chiral cyclopentadienyl ligands bearing oxygen linkers, which were efficient catalysts for C−H arylation of benzo[h]quinolines with 1‐diazonaphthoquinones, affording axially chiral heterobiaryls in excellent yields and enantioselectivity (up to 99 % yield, 98.5:1.5 er). Mechanistic studies suggest that the reaction is likely to proceed by electrophilic C−H activation, and followed by coupling of the cyclometalated rhodium(III) complex with 1‐diazonaphthoquinones. A class of chiral cyclopentadienyl ligands (BOCps) bearing an oxygen linker was developed. The BOCpRh complexes are powerful catalysts in an asymmetric C−H arylation of benzo[h]quinolines with 1‐diazonaphthoquinones to construct axially chiral heterobiaryls. Preliminary mechanistic studies suggest that this reaction is likely to proceed via an electrophilic C−H rhodation and subsequent coupling with 1‐diazonaphthoquinones.